Crystal Structure and Effective Dielectric Response of Ba0.5Sr0.5TiO3–MgO Composites Synthesized In Situ Process. Issue 1 (24th September 2014) - Zhang, Jingji; Ji, Ludong; Jia, Xuanrui; Wang, Jiangying; Zhai, Jiwei; Zhou, Yun; Damjanovic, D.
<x xml:space="preserve">Abstract</x> (1 − x)Ba0.5Sr0.5TiO3(BST)–xMgO composite ceramics have been prepared in situ by a citrate–nitrate combustion process, and their crystal structure and effective dielectric response have been investigated systematically. Results reveal that MgO particles homogeneously disperse in BST particles. Rietveld refinement of X‐ray diffraction data shows that the amount of the incorporation of MgO into BST lattice is increased with increasing the MgO volume fraction (ƒM). It is identified that the incorporation of Mg2+ into B site gives rise to the formation of F centers in the composites. Related with the incorporation of Mg2+ into BST lattice, the permittivity of BST in the composite is strongly dependent on ƒM, which is defined by the relation <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh30vx4m47" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />εBST=a×eb×fM</alternatives>. Also, the high percolation threshold of ƒM = 0.60 is observed, which is well in agreement with the theoretical predictions of the modified effective medium approximation coupled with the spherical inclusion model.